2022
DOI: 10.1002/hbm.25954
|View full text |Cite
|
Sign up to set email alerts
|

Decoding point‐light displays and fully visible hand grasping actions within the action observation network

Abstract: Action observation typically recruits visual areas and dorsal and ventral sectors of the parietal and premotor cortex. This network has been collectively termed as extended action observation network (eAON). Within this network, the elaboration of kinematic aspects of biological motion is crucial. Previous studies investigated these aspects by presenting subjects with point‐light displays (PLDs) videos of whole‐body movements, showing the recruitment of some of the eAON areas. However, studies focused on corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
3
2
Order By: Relevance
“…Whereas studies using point-light displays suggested that motion information was sufficient for action recognition (Dittrich, 1993 ; Ziccarelli et al, 2022 ), we show that form information can also be sufficient for action recognition and adding motion and temporal information can, in some instances, further enhance accuracy. This aligns well with the proposal by Gärdenfors and Warglien ( 2012 ), who suggested that actions could be represented in an “action space” of forces acting upon a conceptual space.…”
Section: Discussioncontrasting
confidence: 71%
“…Whereas studies using point-light displays suggested that motion information was sufficient for action recognition (Dittrich, 1993 ; Ziccarelli et al, 2022 ), we show that form information can also be sufficient for action recognition and adding motion and temporal information can, in some instances, further enhance accuracy. This aligns well with the proposal by Gärdenfors and Warglien ( 2012 ), who suggested that actions could be represented in an “action space” of forces acting upon a conceptual space.…”
Section: Discussioncontrasting
confidence: 71%
“…Whereas studies using point-light displays suggested that motion information was sufficient for action recognition (Dittrich, 1993;Ziccarelli et al, 2022), we show that form information can also be sufficient for action recognition and adding motion and temporal information can further enhance accuracy. This aligns well with the proposal by Gärdenfors and Warglien (2012), who suggested that actions could be represented in an 'action space' of forces acting upon a conceptual space.…”
Section: Form Motion and Temporal Informationcontrasting
confidence: 62%
“…Humans are adept at understanding action when observing biological motion, and in particular, motion that follows human psychophysical constraints (Troje, 2013). In the point-light display paradigm (Johansson, 1973), in which small lights are attached to the joints of an actor in dark clothing, observers watching the moving lights for a few seconds can effortlessly identify the actor's mood (Alaerts et al, 2011) and recognise full-body or hand actions (Ziccarelli et al, 2022).…”
Section: Biological Motionmentioning
confidence: 99%